Bibliometric Analysis of Green Buildings - Loso Judijanto (Westscience Press, 2026)
Green buildings have emerged as a critical strategy for addressing environmental challenges associated with rapid urbanization, energy consumption, and greenhouse gas emissions. Consequently, scholarly interest in green building research has increased substantially over the past two decades. This study aims to map the intellectual structure, research trends, influential contributors, and collaboration patterns within the field of green buildings through a bibliometric analysis. Data were collected from the Scopus database and analyzed using VOSviewer to examine publication networks, keyword co-occurrence, citation patterns, author collaborations, institutional relationships, and country-level partnerships. The findings reveal that green buildings, green building, sustainability, construction industry, and architectural design constitute the core themes of the literature. The overlay visualization indicates a shift in research focus from energy efficiency and building performance toward broader sustainability concerns, including green development, green economy, and sustainable construction. Citation analysis highlights the interdisciplinary nature of the field, with influential studies spanning sustainable materials, environmental management, urban green spaces, and green manufacturing. Co-authorship and institutional analyses identify several leading scholars and universities, particularly from China, which also emerges as the most influential country in international research collaboration. The country collaboration network further demonstrates strong global partnerships involving the United States, the United Kingdom, Australia, and other Asian and European countries.